2022
DOI: 10.1186/s13020-022-00619-2
|View full text |Cite
|
Sign up to set email alerts
|

Alpinetin promotes hair regeneration via activating hair follicle stem cells

Abstract: Background Alopecia affects millions of individuals globally, with hair loss becoming more common among young people.  Various traditional Chinese medicines (TCM) have been used clinically for treating alopecia, however, the effective compounds and underlying mechanism are less known. We sought to investigate the effect of Alpinetin (AP), a compound extracted from Fabaceae and Zingiberaceae herbs, in hair regeneration. Methods Animal model for hair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Kang et al reveal Yangxue Shengfa capsule regulates AGA associated genes, including IGF-1, DKK-1, and TGF-β, and promotes cell proliferation of dermal papilla cells [ 9 ]. Xiao et al verify that alpinetin activates HFSCs to promote hair regeneration through Wnt pathway, and has no toxicity to keratinocytes and fibroblasts [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al reveal Yangxue Shengfa capsule regulates AGA associated genes, including IGF-1, DKK-1, and TGF-β, and promotes cell proliferation of dermal papilla cells [ 9 ]. Xiao et al verify that alpinetin activates HFSCs to promote hair regeneration through Wnt pathway, and has no toxicity to keratinocytes and fibroblasts [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the number of patients with alopecia is increasing rapidly, regardless of gender and age [ 35 , 36 ]. Hair loss is mainly due to the decrease of hair follicle stem cell activity and hair follicle regeneration ability [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Receiving invasive treatments, such as platelet-rich plasma (PRP) injections and hair transplantation, is often difficult, usually need to be repeated and may lead to a costly investment [22][23][24]. Recently, topical herbal preparations have become more widely available because of their higher rates of compliance, fewer side effects, wider active spectrum and less expensive price [25,26]. As a topical TCM preparation, CZX is expected to be widely used in the complementary and alternative treatment of AGA in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Astragaloside IV, the active ingredient of A. membranaceus, inhibits apoptosis-regression catagen in hair follicles, leading to hair regrowth [14]. Clinical studies have shown that prescriptions containing herbs from Zingiberaceae have significant therapeutic effects on alopecia [15]. Nevertheless, the bioactive components and pharmacological mechanism of CZX are still unclear.…”
Section: Introductionmentioning
confidence: 99%